Poultry Nutrition - Tufarelli, Vincenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The aim of this Special Issue is to publish high quality papers concerning poultry nutrition and the interrelations between nutrition, metabolism, microbiota and the health of poultry. Therefore, I invite submissions of recent findings, as original research or reviews, on poultry nutrition, including, but not limited to, the following areas: the effect of feeding on poultry meat end egg quality; nutrient requirements of poultry; the use of functional feed additives to improve gut health and immune status; microbiota; nutraceuticals; soybean meal replacers as alternative sources of protein for poultry; the effects of feeding poultry on environmental impacts; the use of feed/food by-products in poultry diet; and feed technology.